Hubungan Ketidakharmonisan Keluarga dengan Kematangan Emosi Siswa SMK Negeri 1 Ampek Angkek - Juniarti, Nina Fortuna; Afrinaldi, Afrinaldi (MASALIQ, 2023)
This research is motivated by the discovery of how children behave influenced by family disharmony indicating that there are students who are less open to family, students are not given the opportunity to talk in the family, and there is no support for positive activities towards students so that students often blame others. lack empathy, have a big ego. The aim of this study was to determine the relationship between family disharmony and students' emotional maturity. This study uses a Quantitative Correlation approach. The collection of data used in this study through the questionnaire method. The sampling technique used was total sampling by taking a sample of 30 students from a population of 30 students. Data processing techniques that the authors do are data normality test, linearity test and correlation analysis test. The research results obtained based on the correlation analysis test can be concluded that there is an influence between family disharmony (X) and emotional maturity (Y) where a correlation value of 0.699 is obtained at the moderate level which, if expressed as family disharmony, affects the emotional maturity of class XI students at SMK Negeri 1 Ampek Angkek by 0.448 or 45%.